Child sexual abuse: clinical and psychological perspectives - Etty Indriati Etty Indriati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2001)
This article reviews the clinical and psychological effects of children who suffer sexual abuse. Child sexual abuse (CSA) is a forced sexual behavior toward a child, either from the opposite or same sex. The types of child sexual abuse include exhibitionism, vouyerism, kissing, fondling, fellatio and cunnilingus, sexual intercourse, and pornography. The psychological effects of child sexual abuse often last a long time, in the form of anger, anxiety, nightmares, insecure, confused, scared, sad, and behavioral change from good to bad. The clinical effects of child sexual abuse ranges from bleeding in the genital and anus, fissure on anus, enlargement of vaginal and anal openings, and thinning/damaged of the hymen in the vagina. The Indonesian law no. 290 mentions that sexual offender or perpetrator is to be jailed for at most 7 years. It is hoped this review can be used as a general reference for clinicians in obstetrics and gynecology as well as pediatrics, in diagnosing child sexual abuse. This diagnosis is important for helping the abused child to recover and as medical records for law enforcement.Keywords: child sexual abuse, clinical effects, psychological effects